An evaluation of free amino acids as chemotaxonomic markers in Protea L. species - Prosch, Diane (Department of Chemistry, 2023)
One of the major functions of a Botanic Garden should be that of research. When a research laboratory was established at Kirstenbosch National Botanic Garden in 1984, it-was decided to start investigating chemical parameters of our indigenous plants, since this is a field that has not received adequate attention in the past. It was hoped to contribute towards the classification of plants by applying chemotaxonomy or chemosystematics, whereby chemical evidence is incorporated with morphological and other information. The genus Protea L. was an obvious choice for the initial material of such research as it is one of the best-known and most prominent genera of our indigenous flora and its taxonomic revision, based mainly on morphological data, was recently completed by Dr. J. P. Rourke (1980) of the National Botanic Gardens, Kirstenbosch. It was hoped that a phytochemical study of Protea species, whereby their free amino acid composition was determined by paper partition chromatography, might be of use in contributing to its taxonomic classification.